Application of higher order thinking skills (HOTS) of the general education faculty basis for in-service training on test construction - Lantaca, Alhadzmar A. (Universidad de Zamboanga Journal : Official Peer Reviewed Journal Publication, 2014)
Classroom measurement and evaluation is the tradition tool to determine the academic performance of the students. It is incumbent upon the teachers to know if there is learning in the class. The results of the test administered before, during and after will be used as bases to determine learning in the classroom. The teacher should ensure that tests given will measure total performance of the students in the class. A study was designed to determine the extent of application of higher order thinking skills (HOTS) of the general education faculty of the Universidad de Zamboanga. They study intended to identify the extent of application of higher order thinking skills in the management of classroom and evaluation. It measured the significant difference in the extent of application of higher order thinking skills when the respondents ar grouped according to their academic profile. The researcher utilized the descriptive-quantitative method. It is descriptive because the study determined the extent of application of the higher order thinking skills of the general education faculty in assessing the performance of the students. Moreover, the study employed quantitative research method to determine the significant difference in the application of higher order thinking skills when the respondents are grouped according to their academic profile. In this study, there were seven (7) departments included in the study namely: English, Social sciences and humanities, Mathematics, Filipino, Euthenics, NSTP and Science department. A total enumeration was employed in the selection of the respondents in the study. Hence, the researcher employed weighted arithmetic mean and Kruskal Wallis to determine the extent of the application of higher order thinking skills and it's significant difference in the higher order thinking skills among GEC faculty. The findings revealed that there was "slight" application of knowledge and analysis in extent by the GEC faculty. Further, the GEC faculty utilized comprehension and application in their test construction in "low" extent while employment of synthesis and evaluation of their test "very low" in extent. Over-all, the extent of application of the higher order thinking skills by the GEC faculty was "Low" in extent. Educational attainment, academic rank, length of service and and number of teaching preparation did not have any relation to the use of the thinking skills. However, among the different academic rank, assistant professors moderately employed he cognitive level of comprehension in edit test construction to measure student's performance. Since the over-all extent of the use of the thinking skills was relatively low, it became apparent that a training program related to test construction and measurement be devised as part of the continuous learning process of the members of the faculty wi an end view that test construction may be improved alongside classroom teaching.